Number of leaves needed to model leaf area in jack bean plants using leaf dimensions (Bioscience Journal, 2015)
Leaf area estimation models based on linear leaf dimensions are an important method because their application is not destructive to the leaves. For these models to be reliable, it is important that the estimation of model parameters is accurate, and for that to occur, the models must be generated using an adequate sample size (number of leaves). The objective of this study was to determine the number of leaves necessary to accurately model the leaf area of jack beans (Y), determined by digital photos, according to the width of the central leaflet (x), by a power model (Y = axb) generated through an iterative process. Accordingly, an experiment was performed in a 256 m2 area. A total of 745 leaves were randomly collected at six different crop development stages (29, 43, 57, 73, 87 and 101 days after emergence). Each leaf was comprised of a left, central and right leaflet. The width of the central leaflet (x) was measured on the 745 leaves. Leaf area (sum of the area of the left, central and right leaflets; Y) was then determined using a digital photo method. The number of leaves necessary for the estimation of the parameters a and b and the coefficient of determination (R2) of the power model were determined through resampling with replacement. The power model (Å¶ = 4.2049x1.8215, R2 = 0.9701), based on the width of the central leaflet was determined to be adequate for estimating jack bean leaf area. Data collected from a sample of 200 leaves were determined to be sufficient for constructing an accurate power model for the leaf area of jack beans (Y) as a function of the width of the central leaflet (x), based on determinations of leaf area using digital photos.